Загрязнение атмосферы городов газообразными выбросами из канализационных сетей - Бахарева, Анна Юрьевна; Семенов, Евгений Александрович (НТУ "ХПИ", 2014)
Статья посвящена решению актуального задания – обеспечить экологическую безопасность окружающей природной среды с доведением концентраций серо- и азотсодержащих соединений в газообразных выбросах канализационных сетей путем конвертирования этих соединений в экологически безопасные соединения. Для доведения концентрации серо- и азотсодержащих соединений в газообразных выбросах из канализационных сетей до норм ПДК разработан биотехнологический метод.

The article is devoted to solution of topical ecological problem of ensuring of the environmental state with optimization of H2S, SO2 and NH3 concentrations in gasiform throw outs from sewerage networks to bixed MAD by means of its transformation in ecological safety compounds. The methods for bioenvironmental safe of city atmosphere in gasiform throw outs region, containing H2S, SO2 and NH3 have been developed. The effective biotechnology of gasiform throw outs treatment out of sewerage networks has been proposed
Pollution of city atmosphere with gasiform throw outs from sewerage networks
Keywords: газообразные выбросы; экологическая безопасность; биотехнологический метод; канализационные сети; gasiform throw outs; ecological safety; biotechnological detoxication; sewerage networks